Implementasi Sistem Informasi Berbasis Web Pada Noni Foto Studio Jakarta - - UBSI, Fathur Rohman; - STMIK Nusa Mandiri, Nico Savero (APMMI - Asosiasi Profesi Multimedia Indonesia, 2018)
ABTSRACT: The rise of technological developments that affect sales among photography entrepreneurs. Noni Foto Studio still relies on sales made directly at the outlet. To increase turnover for the owner, other marketing is needed that can help in sales at Noni Foto Studio. Therefore, at the writing of this Skirpsi, the writer tries to provide an alternative solution to the problems that occur in the development of Noni Foto Studio's progress by promoting online stores. The alternative solution the author poured in a simple book with the title